Glacier Monitoring for Climate Change Detection in Nunavut - Bell, Trevor; Jacobs, John (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1996)
Summary Nunavut contains approximately 75% of Canada's total glacierized area. The higharctic ice caps have received the most consistent monitoring, whereas glacierson Baffin Island have been monitored for shorter intervals since the 1960s. Although mass balance data for selected Baffin glaciers show no clear trend over the monitoring period, there appears to be reasonable agreement between summer temperature and annual mass balance. In contrast to global warming trends, the Baffin region has experienced a general cooling over the last 30 years, particularly in winter. The cause of this cooling is not fully understood and its impact on the local ice cover is uncertain. In order to address these issues, mass balance observations should be resumed on a suitable glacier as part of an integrated environmental monitoring program in the region.